ANALISIS PERANCANGAN SUPPORT PADA PIPELINE SUATU PROJECT X DENGAN MENGGUNAKAN PROGRAM CAESAR II - Dedy Krisbianto; Agung Nugroho (KALPIKA, 2022)
The design of a good and safe piping system is needed to ensure the continuity of the production process andensure safety. To overcome the magnitude of the stress that occurs due to loading, analysis is needed. In thisfinal project, the stress of the High Pressure Vent Pipeline will be analyzed with the CAESAR II approachand with the Allowable Stress limit of ASME B31.3. In this final project, a discussion of the piping path fromthe Pig Launcher outlet to the Pig Receiver inlet is carried out with line number ”-PG-KT-A02A-016, 8”-PG-KT-A02A-027, 2”-02-BV-024 dan 2”-02-GLB-004. The design starts from collecting data, analyzing thepipe thickness (pipe schedule) from the type of material used in the initial design which refers to the ASMEB31.3 Process Piping standard. In the redesign, the support distance is below the maximum span limit,which is less than 8m so that it does not provide deflection and excessive stress on the piping system.